Offshore fears and onshore risk exchange rate pressures and bank volatility contagion in the Peoples Republic of China Jennifer Lai and Paul D McNelis. (Economics working papers, 2019)
The findings contrast with one view that the offshore spot market for the currency, listed as CNH, is a shock absorber for the PRC financial system. The analysis suggests that further offshore exchange market movements arising out of news, such as increasing trade friction with the United States, will generate greater volatility in the PRCs banking sect